Calcium Sulfoaluminate Based Concrete - Mechanical Characterization. Issue 3 (February 2019) - Bertagnoli, Gabriele; Tondolo, Francesco; Canonico, Fulvio; Malavisi, Marzia; Anerdi, Costanza; Buzzi, Luigi; Mancini, Giuseppe
Abstract: In the last few years, sustainable cement manufacturing has been under the spotlight. Finding alternative cements while maintaining or improving current performance standards is scientist's effort. In particular, calcium sulfoaluminate (CSA) cements represent a very promising alternative compared to ordinary Portland cement (OPC) because of their high early strength, excellent durability, good performance in aggressive conditions, low energy consumption as well as reduced CO2 emissions. This paper presents the results of several experimental tests, planned in order to characterize the thermo-hygro-mechanical behaviour of CSA-based concrete since first minutes after casting. Twelve different tests were carried out: compressive strength and indirect tensile tests, stress-strain curve plot, rheology (creep and shrinkage) tests, water porosity, semi-adiabatic temperature evolution during hardening, fatigue test. Different curing periods were selected in order to analyse changes in strength. Experimental results show that CSA-based cements can be formulated to produce durable concrete with physical properties comparable to those of common classes of Portland cement concrete.